Реалізація каузації у неформальних комунікативних ситуаціях медичного дискурсу - Кононова, Д.В. (Центр наукових досліджень та викладання іноземних мов НАН України, 2008)
Статья посвящена дискурсивному и конверсационному анализу каузативных ситуаций в сфере медицины. Конфигурация социальных ролей, выбор речевых актов, коммуникативные стратегии и тактики, невербальные элементы коммуникации рассматриваются как компоненты каузативного дискурса. The article contains discourse and conversation analysis of causative communication situations in medicine. Social roles configuration, choice of speech acts, communication strategies and tactics, non-verbal means are viewed as essential components of causative discourse.